Pelaksanaan Lelang Jaminan Fidusia Sebagai Jaminan Kredit Dalam Perbankan - Agustina Purwasih; I Gusti Agung Wisudawan (Bagian Hukum Bisnis Fakultas Hukum Universitas Mataram, 2023)
Purpose of this research are to know implementation of fiduciary collateral auction as fiducia guarantee in Indonesian banking and to know creditor legal responsibility on the auctioned fiducia collateral. This research was normative legal research which applied statute and conceptual approaches. Result of this study, are, first: implementation of auction on fiducia collateral in Indonesian banking is conducted in two ways are conventionally and electronically (e-auction). Type of auction on fiducia collateral is included in execution auction which conducted under the general auction which KPKNL assistance or it also can be done by unofficially according to agreement between parties.Second, banking have been complete his responsibility according to the law on auctioned fiducia collateral such as registering fiducia collateral as fiducia object of guarantee, warning the customer if broke his promises, communicating mediation and negotiating with the customer if problems occurred, providing information and auction announcement thus the customer aware if the guarantee object will be put into an auction, and also restoring the remaining results of the execution of fiduciary collateral objects that exceed the value of the guarantee to the debtor.